A Cultura como alavanca de inclusão e de participação social: uma nova geração de políticas públicas de proximidade - Paula Guerra (2007)
This communication proposes to discuss the role that culture, supporting social inclusion and participation, may now play in major Portuguese cities, with the backdrop of the current discussion about public proximity policies and the need of the State seek to act increasingly in a logic of cooperation and partnership with other agencies and institutions with a view to streamlining and optimizing their interventions. The first analytic axis aims to explore the increasingly wider dimension of the concept of culture, which today stands as an aggregator and enhancer element of many social dynamics. Currently, and drawing on cultural, artistic and creative activities, you can explore innovative solutions to promote social participation of agents, new formats education / training, enhance the leisure component in the everyday experiences of social support, etc.. A second axis, will focus on redesigning the current importance of public proximity services and the contribution that culture can take over there. We will identify new innovative approaches to this type of projects, taking as indispensable the need for the State to act increasingly in a logic of partnership and cooperation. Thus, taking culture as a lever for development, we consider intervention clues that are based on the confidence in the capabilities of the local people and the ability to combine them the best way possible, defending the "local " as a space for expression of willingness to participate in future space and in concrete practical test of innovative socio-economic formulas.